Nanotechnology : health and environmental risks - Shatkin, Jo Anne, editor (Boca Raton : CRC Press, 2013)
"This book introduces the use of risk analysis as a tool for responsible environmental decision making in nanotechnology development, providing concise, yet informative, narratives on the topics of toxicology, occupational health and safety, and environmental implications of nanotechnology. This new edition presents new perspectives and provides updates on the technical, societal, and regulatory developments in the field. The text presents historical perspectives, provides an overview of current concerns, summarizes international efforts to address risk, describes methods for evaluating nanotechnology risks, and presents current and proposed approaches for managing those risks"--provided by publisher